2012
DOI: 10.1097/sla.0b013e3182363ff9
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Results of a Randomized, Observation-Controlled, Phase III Trial of Adjuvant Interferon Alfa-2b in Hepatocellular Carcinoma After Curative Resection

Abstract: In this study, adjuvant IFNα-2b did not reduce the postoperative recurrence of viral hepatitis-related HCC. More potent antiviral therapy deserves to be explored for this patient population. This study is registered at ClinicalTrials.gov and carries the identifier NCT00149565.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
95
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(100 citation statements)
references
References 41 publications
4
95
1
Order By: Relevance
“…One of the meta-analysis reported by S. Breitenstein [29] included one trial less than ours. And this trial [28] was published recently by LT Chen and its conclusion was contrary to the trials which were included in Breitenstein's report [29]. Meanwhile, samples in Chen's [28] report were much larger than any other RCTs [8,10,[21][22][23][24]27], which were all included in our metaanalysis.…”
Section: Discussioncontrasting
confidence: 48%
See 2 more Smart Citations
“…One of the meta-analysis reported by S. Breitenstein [29] included one trial less than ours. And this trial [28] was published recently by LT Chen and its conclusion was contrary to the trials which were included in Breitenstein's report [29]. Meanwhile, samples in Chen's [28] report were much larger than any other RCTs [8,10,[21][22][23][24]27], which were all included in our metaanalysis.…”
Section: Discussioncontrasting
confidence: 48%
“…In recent years, several randomized controlled trials [8,10,[21][22][23][24][25][26][27][28] have revealed that IFN can have some influence on the recurrence of HCC. Some of them give a promising conclusion that the adjuvant IFN can reduce recurrence, while the others hold the opposite opinion.…”
Section: Original Papersmentioning
confidence: 99%
See 1 more Smart Citation
“…Various postoperative interventions, such as adjuvant therapy with interferon, Vitamin E or K2, or I 131 , are used to reduce the incidence of tumor recurrence after curative treatment (6,7). The adjuvant application of interferon (7)(8)(9)(10) and antiviral treatment (11,12) seems promising but should be confirmed in further multi-center phase III clinical trials.…”
Section: Introductionmentioning
confidence: 99%
“…2 Unfortunately, recurrence after resection occurs in up to 80% of patients within five years following surgery, which together with concomitant hepatic decompensation, are the main causes of death. 3 Several adjuvant treatments including arterial infusional chemotherapy, 4 I 131 lipiodol, 5,6 and interferon 7,8 have been used. Unfortunately, the clinical use of these adjuvant therapies is either controversial or requires further evaluation.…”
Section: Introductionmentioning
confidence: 99%